2016
DOI: 10.1590/1806-9061-2016-0260
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Manipulation Mid-term Broiler Chicken Embryogenesis: Effect on Muscle Growth Factors and Muscle Marker Genes

Abstract: Thermal manipulation (TM) during broiler chicken embryogenesis has been shown to promote muscle development and growth. However, the molecular bases of promoting broiler muscle development and growth are not fully understood. The aim of this study was to investigate the molecular bases of muscle growth and development in broiler chickens subjected to TM. This included the investigating of the changes in mRNA expression levels of muscle marker genes, namely MyoD, myogenin, paired box transcription factor (Pax7)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 50 publications
2
11
0
Order By: Relevance
“…In the current study, TM was achieved by raising the incubation conditions to 39 • C and 65% RH for 18 h/day from ED 10 to 18. Previous studies used similar TM treatment parameters, including incubation at 39 • C for 18 h/day from ED 7-11, at 38.5 • C from ED 16 to 18 and at 39 • C for 18 h/day from ED 12 to 18, and these parameters were shown to significantly enhance BW as well as upregulate expression of muscle marker genes [27,[31][32][33]. The duration of TM was reported to affect thermotolerance acquisition in broilers, and different TM treatments led to differences in physiological parameters as well as varied mRNA expression profiles of heat shock genes [34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, TM was achieved by raising the incubation conditions to 39 • C and 65% RH for 18 h/day from ED 10 to 18. Previous studies used similar TM treatment parameters, including incubation at 39 • C for 18 h/day from ED 7-11, at 38.5 • C from ED 16 to 18 and at 39 • C for 18 h/day from ED 12 to 18, and these parameters were shown to significantly enhance BW as well as upregulate expression of muscle marker genes [27,[31][32][33]. The duration of TM was reported to affect thermotolerance acquisition in broilers, and different TM treatments led to differences in physiological parameters as well as varied mRNA expression profiles of heat shock genes [34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Thermal manipulation (TM), which involves altering incubation temperature at certain intervals during embryonic development, has been extensively reported to alleviate the effects of heat stress in broilers and enhance muscular growth [25][26][27]. Moreover, TM broilers were found to exhibit a modulated genome-wide gene expression profile upon exposure to heat stress [28].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, previous studies reported that chicks incubated at 39.5 °C for 3 h/d during ED 8–10 had unaffected weights during post-hatch life. However, other studies reported that increasing the incubation temperature to 38.5 °C during ED 16–18 and to 39 °C 18 h/d during ED 12–18 resulted in increased broiler body weights [34,35]. Furthermore, egg incubation at 39.5 °C for 12 h/d during ED 7–16 led to increased myofiber diameters and enhanced muscle growth, up to 35 days of age [36].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TM immediately affects miRNA expression profiles of breast and hind muscles of chicken embryos and is associated with minor long term expression of miRNAs broiler chickens [19]. However, the molecular bases for promoting muscle development and growth requires further investigation [12, 13, 16, 20]. Therefore, the current study aimed to investigate the effect of different daily TM conditions, namely TM 1 (38.5°C for 18 h), TM 2 (39°C for 18 h), TM 3 (39.5°C for 18 h) and TM 4 (40°C for 18 h) during embryonic days (ED) 12 to 18, on body (BW) and internal organ weights and expression of muscle growth and transcription factor genes of broiler chickens.…”
Section: Introductionmentioning
confidence: 99%